Long‐term evaluation of the efficacy of digital dermatoscopy monitoring at a tertiary referral center. (May 2017) - Rinner, Christoph; Tschandl, Philipp; Sinz, Christoph; Kittler, Harald
Summary: Background and objectives: We examined the value of monitoring patients with multiple nevi using sequential digital dermatoscopy imaging at a tertiary referral center. Patients and methods: This is a retrospective cohort study including 2, 824 patients and 23, 241 monitored lesions. We calculated trends in key parameters such as the number of melanomas and nevi monitored and excised. Results: During follow‐up, we excised 1, 266 lesions in 709 patients, including 146 (11.5 %) melanomas. The percentage of in situ melanomas detected at follow‐up was significantly higher than at baseline (46.6 % versus 23.4 %, p ≤ 0.001). The risk of detecting a melanoma during follow‐up was higher for patients with a melanoma at baseline, compared to those without (relative risk: 3.59, 95 % CI: 2.15 to 6.00). The number of documented lesions showed a positive correlation with the benign/malignant ratio, and excisions at baseline decreased significantly over the course of the study period. Conclusion: Digital dermatoscopy monitoring improves the detection of thin melanomas in patients with multiple nevi. Patients with a melanoma at baseline are at an increased risk of developing a melanoma during follow‐up and should therefore be a target group for sequential dermatoscopy imaging.